New Family Values: Liberty, Equality, Diversity - Struening, Karen (Rowman & Littlefield Publishers, 2002)
How many different kinds of families are there? New Family Values provides a critical analysis of scholars and authors who argue that law and policy should be used to foster one model of the family—the intact, two-parent, heterosexual family. Karen Struening argues that this position does not adequately address the problem it supposedly solves—family dissolution—and unnecessarily constrains personal liberty. Healthy families may be necessary for civic unity and individual stability, but there can be many different kinds of families.